2022
DOI: 10.18203/2394-6040.ijcmph20222028
|View full text |Cite
|
Sign up to set email alerts
|

Perception of community medicine as a curriculum and career option among medical students

Abstract: Background: In India, medical curricula have not been kept up to date with changes in public health, demography, and health policies. Clinicians serve as role models for students in medical colleges, and CM is not seen as an appealing career option by students. Hence this study was designed to analyze the perceptions and attitudes of medical undergraduates towards the relevance of CM as a future career option.Methods: This cross-sectional study was done in a Kasturba medical college, Manipal academy of higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…The findings of the study showed that most students perceived CM as an essential subject that provided a holistic view of public health and its importance. This finding was aided by similar result that was found in study done by Muthamilan OL et al (7) Despite that, the study found that the students' interest in CM correlated negatively with their career preference for the same, only three students chose CM as their career preference. Similarly, studies done by Guraya SY et al (8)…”
Section: Discussionsupporting
confidence: 81%
“…The findings of the study showed that most students perceived CM as an essential subject that provided a holistic view of public health and its importance. This finding was aided by similar result that was found in study done by Muthamilan OL et al (7) Despite that, the study found that the students' interest in CM correlated negatively with their career preference for the same, only three students chose CM as their career preference. Similarly, studies done by Guraya SY et al (8)…”
Section: Discussionsupporting
confidence: 81%